Endocrine-disrupting substances: I. Relative risks of PFAS in drinking water. (17th March 2023) - Tomei Torres, Francisco Alberto; Masten, Susan J.
Abstract: Concentrations of per and polyfluorinated alkyl substances (PFAS) in drinking water are significantly lower than in vivo levels of the native target hormone. These concentrations are orders of magnitude lower than the hormone in question, particularly when corrected for transactivation. A pregnant woman can excrete about 7, 000 μg/day of total estrogens. A low-dose oral contraceptive pill contains 20 μg estradiol. Soy-based baby formula contains phytoestrogens equivalent to a low-dose oral contraceptive pill. A woman on a low-dose oral hormone replacement therapy consumes about 0.5–2 mg/day of one or more estrogens. The levels of endocrine-disrupting substances (EDSs) exposure by oral, respiratory, or dermal routes have the potential to make removing PFAS from drinking water due to its estrogenic activity divert valuable resources. These levels become even less of a threat when their estrogenic potencies are compared with those of the target hormones present as contaminants in water and even more so when compared with levels commonly present in human tissues. The fact that PFAS constitute a tiny fraction compared to exposure to phytoestrogens makes the effort even more insignificant. If PFAS are to be removed from drinking water, it is not due to their estrogenic activity. HIGHLIGHTS: The levels of EDSs exposure by oral, respiratory, or dermal routes are significant. Exposure to estrogenic compounds is primarily through diet, not drinking water. PFAS in drinking water typically does not pose a threat due to estrogenic activity. PFAS in drinking water may pose a threat at contaminated sites, warranting remedial action. If PFAS is to be removed from drinking water, it is due to toxicity, not estrogenic activity.